Comparative radiopacity of pediatric dental restorative materials - Kuter Berna; Uzel Ilhan (Balkan Stomatological Society, 2022)
Background/Aim: Radiopacity of dental restorative materials is significant to detect secondary caries, overhangs, and voids. This study aimed to evaluate whether radiopacity of dental restorative materials used in pediatric dentistry was sufficient. Material and Methods: Specimens of 2 mm thickness and 4 mm diameter were prepared in the plastic molds. Six composite materials, one compomer material, and one conventional glass ionomer cement were used and three specimens of each material were prepared. Three radiographs were taken from dental restorative materials and aluminum step wedge. Digital images obtained were recorded. Mean gray values of the dental restorative materials and aluminum step wedge were measured on digital radiographs. Results: All composite resins displayed higher radiopacity values than an equal thickness of 2 mm Al. Posterior composite (201.62±1.99 MGV) showed higher radiopacity value than the anterior composite (86.19 ±1.45 MGV). There was no significant difference in radiopacity values of different shades of the same composite. There was no significant difference in radiopacity values between glass ionomer cement and compomer. Glass ionomer cement showed higher radiopacity value (8.11 mm Al) than anterior composite (5.31 mm Al). Conclusions: Radiopacity values of dental materials used in this study were sufficient. Both resin materials and the glass ionomer cement had sufficient radiopacity values. Posterior composite showed the highest radiopacity value. Radiopacity values were not affected by different shades.